1996
DOI: 10.1111/j.1476-5381.1996.tb15273.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sympathetic purinergic neurotransmission in the guinea‐pig isolated vas deferens by the novel ecto‐ATPase inhibitor ARL 67156

Abstract: 1 Field stimulation of the sympathetic nerves of the guinea-pig isolated vas deferens with trains of pulses for 20 s at 1-8 Hz produced characteristic biphasic contractions. The effect of the novel ectoATPase inhibitor, 6-N,N-diethyl-D-13,y-dibromomethyleneATP (ARL 67156, formerly known as FPL 67156), on the magnitude of the initial, predominantly purinergic peak of this response was studied in order to determine the influence of enzymatic degradation of adenosine 5'-triphosphate (ATP) on its action as a neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 27 publications
10
53
0
Order By: Relevance
“…In bladders exhibiting DO either excess ATP is released, or ATP is less effectively broken down in the junction. Evidence for the latter possibility was obtained when it was shown that ectoATPase activity is reduced in detrusor samples from human DO bladders (Harvey et al, 2002), corroborated by other observations that show enhancement of the nerve-mediated contraction in the presence of ectoATPase inhibitors such as ARL 67156 (Westfall et al, 1996(Westfall et al, , 1997. This observation provides one target for reducing contractions in the overactive bladder, but has yet to be clinically exploited.…”
Section: Figure 2 Near Heresupporting
confidence: 58%
“…In bladders exhibiting DO either excess ATP is released, or ATP is less effectively broken down in the junction. Evidence for the latter possibility was obtained when it was shown that ectoATPase activity is reduced in detrusor samples from human DO bladders (Harvey et al, 2002), corroborated by other observations that show enhancement of the nerve-mediated contraction in the presence of ectoATPase inhibitors such as ARL 67156 (Westfall et al, 1996(Westfall et al, , 1997. This observation provides one target for reducing contractions in the overactive bladder, but has yet to be clinically exploited.…”
Section: Figure 2 Near Heresupporting
confidence: 58%
“…The first reaction of hydrolysis of ATP is catalyzed by ecto-NTPDases (E-NTPDases), a family of enzymes reviewed by Zimmermann (2000). E-NTPDases catabolize ATP to ADP and ATP/ADP to AMP, and they can be inhibited by ARL 67156 (Crack et al, 1995;Westfall et al, 1996Westfall et al, , 2000Mihaylova-Todorova et al, 2002). Consistent with the idea that BzATP is similarly metabolized as ATP before it can activate GIRK channels, ARL 67156 abolished BzATP-induced currents (Fig.…”
Section: Bzatp Is Converted To Adenosine By a Combined Action Of Ectosupporting
confidence: 53%
“…The effects of cooling and of the specific ecto-ATPase inhibitor, ARL 67156, on EJPs have been suggested to be consistent with a role of the ecto-ATPase in modulating purinergic neurotransmission in the rodent vas deferens (Cunnane and Manchanda, 1988;Westfall et al, 1996). However, there have been no reports of direct estimations of the activity of this enzyme in the above conditions, i.e., change of temperature and exposure to ARL 67156, in the rodent vas deferens.…”
Section: Discussionmentioning
confidence: 88%